(3EbJUGO GdeYQaI (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2014)
(3eGgjI GdeYQaI(B- (3YedjGJ EOGQI GdeYQaI(B- (3EbJUGO GdeYQaI(B- (3GdJLGQI GdEdcJQhfjI(B- (3GdJShjb GdEdcJQhfj hGdJShjb YHQ GdCfJQfJ(B- (3eLJeY GdeYQaIs
Keywords: (3EbJUGO GdeYQaIs; (3GdeYQaIs; (3JcfhdhLjG GdeYdheGJs